Planning of Pedestrian Facilities and Integrated Crossing Based on the Concept of Active Living on C UNTIRTA - Bethary, Rindu Twidi; Intari, Dwi Esti; Pradana, Muhammad Fakhruriza; Maharani, Anisah Yogiana (JURUSAN TEKNIK SIPIL, 2025)
Campus C of Sultan Ageng Tirtayasa University does not yet have adequate pedestrian facilities and crossing facilities at the main gate are not yet available so that the analysis of pedestrian facilities and crossing facilities is carried out with the aim of knowing the types of pedestrian facilities and road crossing facilities needed and making pedestrian facility designs that use the concept of active living. Campus C of Sultan Ageng Tirtayasa University is located on Jalan Ciwaru Raya No. 25, Cipare, Serang City. Data collection was conducted using direct observation method. The data collected included pedestrian volume, traffic volume, crosswalk volume, and road geometric data. The results showed that the recommended crossing facility for segment 1 on Jalan Ki Ajurum No. 2 is a zebra crossing with waiting stalls with a maximum PV2 result of 1748717534 (1 × 109). While for segment 2 on Jalan Ciwaru Raya No. 25 is a zebra crossing with a maximum PV2 result of 1615465208 (1 × 109). The recommended effective width of sidewalks within Campus C of Sultan Ageng Tirtayasa University is divided into 2 sizes, namely 2 meters and 2.5 meters. Complementary facilities that support the concept of active living that can be recommended are by providing seating, lighting, shading in the form of trees, trash bins, drinking water taps at several points, and special paths for people with disabilities.